QUALITY ANALYSIS OF SERVICE WITH SERVQUAL (SERVICE QUALITY) METHOD IN TINI CAKE CATERING & COOKIES MALAYSIA RESTAURANT - Silmi Yuthika Sany; Kuncorosidi Kuncorosidi; Mutqi Sopiawadi (STIESA Press, 2020)
Restaurant Catering Tini Cake & Cookies is a homemade catering based restaurant that provides buffet food in Malaysia. The purpose of this study is to analyze on service quality and determine the attributes that become a priority in improving the quality of restaurant service Tini Cake & Cookies. The methode used in this research is Servqual (Service Quality). This method measures the quality of service and be used to analyze the cause of service problem and dimensions used in this research are tangibles, reliability, responsiveness, empathy, and assurance. From the research result can be seen that the quality of service at the restaurant has not meet the need and desires of consumers. Based on the Servqual analysis shows that the attribute of improvement priority is attribute RES3 (the speed of the restaurant in responding to conditions when seat is full) from Responsiveness dimension. Based on the assesment, the attribute has the greatest negative gap value of -0,64 so it needs to be improved from human side.